Comparative profitability of agroecological practices in Ethiopian wheat farming - Ng-Ang-A, Stanley Karanja; Ogutu, Sylvester Ochieng; Tibebe, Degefie; Akinyi, Devinia; Mockshell, Jonathan (Frontiers Media, 2025)
Introduction: Agroecology is increasingly promoted as a pathway to sustainable food production, aiming to maximize natural resource use while minimizing external inputs with harmful environmental effects. Agroecological practices can enhance farm productivity while ensuring environmental sustainability. However, these practices often require higher initial investments compared to business-as-usual (BAU) practices, and their profitability and relative risks are not well studied. This research evaluates the profitability and risk of adopting agroecological practices among wheat farmers in Ethiopia.